Pengaruh Konsentrasi Bio-urine Sapi dan Durasi Skarifikasi Terhadap Perkecambahan Tanaman Nila (Indigofera sp) - Nuryah K.A.; Sudirman Sudirman; Amrullah Amrullah; Asrul Hamdani; Cecep Budiman (Indonesian, 2021)
This research aims to determine the effectduration of scarification and concentration of cow bio-urine on Indigofera sp seed germination. This research has been conducted from January 2021 to February 2021 located in the integrated laboratory of the Faculty of Animal seience and Fisheries Campus II Biling Monte, University of Samawa (UNSA), Sumbawa Regency. Using factorial completely randomized design (RAL Factorial) with 2 factors, the first factor was 4 treatments K0 (100% aquadest concentration), K1 (100% Bio-urine), K2 (90% Bio-urine + 10% aquadest) and K3 (80% Bio-urine + 20% aquadest) and the second factor was 3 treatments T1 (15 minutes), T2 (20 minutes) and T3 (25 minutes). The observed variable were the height of sprouts and the percentage of sprouts. The results showed that the highest sprout height variable in this research was the K3 concentration with an average of 61.84 mm, for the best duration was T3 with an average of 54.33 mm. Meanwhile, for the interaction between concentration and duration, the best is K3T3, namely 13.06 mm. Concentration and duration of scarification had a very significant effect (P<0.01) on the height of sprouts. The best sprouts percentage variable in this study was the K1 concentration with an average of 45%. While the best duration is T2 with an average of 36.08%. Meanwhile, for the interaction between concentration and duration, the best is K3T2 which is 86.93%. Concentration and duration of scarification had a very significant effect (P<0.01) on the percentage of sprouts. Meanwhile, for the interaction between concentration and duration, the best is K3T2 which is 86.93%. Concentration and duration of scarification had very significant effect (P<0.01) on the percentage of sprouts. Meanwhile, for the interaction between concentration and duration, the best is K3T2 which is 86.93%. Concentration and duration of scarification had a very significant effect (P<0.01) on the percentage of sprouts.